Mecânica articular de membros inferiores na fase de apoio da marcha após 4 a 8 anos da cirurgia de reconstrução do ligamento cruzado anterior - Stoelben, Karine Josibel Velasques (2017)
The anterior cruciate ligament reconstruction (ACLR) is the sixth most common orthopedic surgery in United States, and has been performed in 65% of individuals who injured the anterior cruciate ligament (ACL). The ACLR is indicate for young and active population and aim to restore the previous physical activity level. However, lower limb movement asymmetries persist long-term after ACLR, and the principal long-term consequences are re-injuries and osteoarthritis development. Changes in loading between joints seem to be a gait compensation after ACLR. Furthermore, it is unclear how ACLR individuals compensate in faster walking speeds. Thus, the aim of the present study was to identify differences between groups (ACLR individual’s vs healthy controls), legs and walking speeds for ankle, knee and hip joint moments in three planes throughout the stance phase of the gait cycle. Forty men between 25 and 45 years old took part of the study. Twenty of them had undergone ACLR 4 to 8 years before the assessment and twenty others without any lower limb injuries. Anamnesis, lower limb functional tests and gait analysis were assessment. For this, questionnaires, kinematic analysis system, force plates and photocells were used. Stance phase of gait were compare across plotting mean and 95% confidence intervals. Significant differences were established when a consecutive 5% of gait cycle in which 95% confidence interval did not overlap. We found walking speed influence for knee and hip in sagittal plane and for ankle in frontal plane. Transverse plane had differences between groups, legs and walking speeds. The most notable results are between groups, reconstructed leg had lower moment magnitude than no-preferred leg of healthy controls in fast speed for ankle and knee. The contralateral leg of ACLR group had higher moment magnitude than preferred leg of healthy controls in self-select walking speed for knee and hip. These results suggesting that there are compensations by others joints after ACLR for minimizing reconstructed leg load. Additionally, faster walking speeds change lower limb joint moments pattern.